Local Citation Analysis of Graduate Biology Theses: Collection Development Implications. - Laura Newton Miller (Issues in Science and Technology Librarianship, 2011)
This paper will focus on the citation analysis of graduate masters theses from Carleton University's Biology Department with implications for library collection management decisions. Twenty-five masters theses were studied to determine citation types and percentages, ranking of journals by frequency of citation and by number of authors citing, and by age range of journal citations. The researcher examined what percentages of journals were accessible through the local catalogue and conducted further analysis of specifics regarding unavailability. Journals were also ranked by subject specialty. Results indicate that although the library has many of the journal articles cited, knowing why a citation was unavailable is useful for establishing future purchasing needs. Although journal rankings are traditionally performed using total number of citations, the ranking by number of authors citing a source can make a difference when compiling core journal lists. The researcher concludes by discussing implications for collection development in times of fiscal constraint. [ABSTRACT FROM AUTHOR]